Avaliação das atividades angiogênica e antiangiogênica, genotóxica e antigenotóxica e mutagênica e antimutagêrnica da solução aquosa de Caesalpinia Férrea (TUL.) Martius (Jucá) - Oliveira, Kênia dos Santos (2014)
Caesalpinia iron Martius ex. Tul var. iron is a tree that belongs to the family Legumoninosae, distributed in tropical and subtropical regions, grows throughout Brazil in the North and Northeast regions, known as ironwood, Jucá, Ibirá-obi-ita Imirá, Muira-obi. Some of the therapeutic properties of Caesalpinia iron have been described and include treatment of wounds and bruises, relief from chronic cough and asthma. The fruits have been used in the treatment of diabetes and in the prevention of cancer, the roots are used as antipyretic and antidiarrheal, and the decoction is anticatarral timber and healing the stem bark is still used as a decongestant for the treatment of diarrhea and enterocolitis , still showing possible benefits on the cardiovascular system of users. This study evaluated the angiogenic / antiangiogenic genotoxic / mutagenic antigenotoxic and / antimutagenic of aqueous solution of Caesalpinia Iron (Tul) martius (Juca) using laboratory tests "in vivo", as an experimental model to chorioallantoid membrane of embryonated chicken eggs activities, Test for mutagenicity in the Ames Salmonella typhimurium (strains TA 100 and the micronucleus test in mouse bone marrow. Our results indicated that the aqueous solution of the fruit of jucá concentration of 20 g / ml promoted the angiogenic process in the chorioallantoic membrane of embryonated hen eggs. micronucleus test indicated the absence of mutagenic and cytotoxic in the dose of 200.0 mg.kg-1 body weight per activity, since there was no increase in the frequency of micronucleus in polychromatic erythrocytes, as compared to the group negative control. you Mutagenicity Test results showed that the solution jucá was not mutagenic to Salmonella typhimurium TA100 strain in any of the doses tested.